2003
DOI: 10.1001/archotol.129.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Wolfram Syndrome Type 1 Gene (WFS1) Define a Clinical Entity of Dominant Low-Frequency Sensorineural Hearing Loss

Abstract: Dominant LFSNHL is most commonly caused by mutations in the Wolfram syndrome type 1 gene (WFS1). Mutations in WFS1 also cause a rare recessive syndromic form of hearing loss known as Wolfram syndrome or DIDMOAD (diabetes insipidus, diabetes mellitus, optic atrophy, and deafness). Routine newborn hearing screening methods will not typically identify hearing loss affecting frequencies below 2000 Hz; thus, children at risk must be specifically monitored. Genetic counseling and genetic testing may be useful in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…In DNFA6/14/ 38 there is no or only mild progression of hearing loss. Some patients have also reported tinnitus, but none reported vertigo or dizziness (Young et al 2001;Lesperance et al 2003;Pennings et al 2003). In the present study, two out of nine patients noticed tinnitus, but none had progression of hearing loss or vertigo, in line with the previously reported phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…In DNFA6/14/ 38 there is no or only mild progression of hearing loss. Some patients have also reported tinnitus, but none reported vertigo or dizziness (Young et al 2001;Lesperance et al 2003;Pennings et al 2003). In the present study, two out of nine patients noticed tinnitus, but none had progression of hearing loss or vertigo, in line with the previously reported phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…In some patients, however, audiometric thresholds at higher frequencies deteriorate with increasing age, resulting in horizontal HL in middle age and high-frequency HL above the age of 60 years [8,22]. Some patients have also reported tinnitus, but none reported vertigo or dizziness [8,23,24]. In this study, the affected family members carrying the A844T mutation showed no subjective progression of hearing impairment or vestibular symptoms, which is consistent with the symptoms of DFNA6/14.…”
Section: Discussionsupporting
confidence: 84%
“…Hearing impairment (HI) in Wolfram syndrome is progressive and mainly affects the high frequencies [Cremers et al, 1977;Higashi, 1991], with affected females showing significantly more HI than affected males [Pennings et al, in press]. In contrast, HI associated with DFNA6/14 only affects the low frequencies and it shows little or no progression [The Vanderbilt University Hereditary Deafness Study Group, 1968;Kunst et al, 1999;Brodwolf et al, 2001;Bom et al, 2002;Huygen et al, 2002;Lesperance et al, 2003;Pennings et al, 2003]. DFNA1 (MIM# 124900) is currently the only other known deafness locus that affects the low frequencies [Lynch et al, 1997].…”
Section: Introductionmentioning
confidence: 99%